Efficient blockchain system based on proof of segmented work - Ahmed, Rashad; Ahmad, Alif; Monem, Maruf; Jumana (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.